The Rise of Islamic Digital Pedagogy: A Systematic Review of Blended-PJBL Trends within Indonesia's Independent Curriculum (2021-2026) - Akyunil Ummah; Tri Wahyudi Ramdhan; Mufaizin Mufaizin (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2026)
The current era of digital disruption has triggered a significant transformation in the Islamic Religious Education (PAI) system, particularly driven by the Independent Curriculum (Kurikulum Merdeka) which requires adaptive pedagogical innovation. This study aims to synthesize the evolutionary trends of digital learning in PAI, evaluate the effectiveness of various digital tools, and analyze the integration of blended learning models during the 2021–2026 period. Using a Systematic Literature Review (SLR) approach based on the PRISMA protocol, this study examined 18 selected scientific articles from an initial pool of 840 publications identified through Google Scholar and Crossref databases. The findings reveal a growing shift toward the concept of Islamic Digital Pedagogy, where the Blended Project-Based Learning (Blended-PjBL) model emerges as one of the most effective pedagogical instruments. This model enables the integration of asynchronous digital learning with collaborative real-world projects, allowing students not only to understand theoretical concepts but also to internalize Islamic values through practical social engagement that supports the Pancasila Student Profile (P5). Furthermore, the use of digital platforms such as Wordwall, Quizizz, Canva, and CapCut enhances student engagement and encourages learners to become active producers of digital learning content. Despite these opportunities, the transformation of digital learning in PAI also faces several challenges, including disparities in teachers’ digital literacy and ethical concerns related to the use of Artificial Intelligence in learning environments. In this context, the concept of fiqh al-muamalah al-raqmiyyah is proposed as an ethical framework to guide responsible digital interaction and ensure that technological innovation remains aligned with Islamic moral values. The findings of this study highlight the practical importance of integrating pedagogical innovation, digital literacy, and ethical guidance in shaping the future of Islamic education in the Society 5.0 era.